Independent regulation of basal neurotransmitter release efficacy by variable Ca²+ influx and bouton size at small central synapses. - Yaroslav S Ermolyuk; Felicity G Alder; Christian Henneberger; Dmitri A Rusakov; Dimitri M Kullmann; Kirill E Volynski (PLoS Biology)
The efficacy of action potential evoked neurotransmitter release varies widely even among synapses supplied by the same axon, and the number of release-ready vesicles at each synapse is a major determinant of this heterogeneity. Here we identify a second, equally important, mechanism for release heterogeneity at small hippocampal synapses, the inter-synaptic variation of the exocytosis probability of release-ready vesicles. Using concurrent measurements of vesicular pool sizes, vesicular exocytosis rates, and presynaptic Ca²⁺ dynamics, in the same small hippocampal boutons, we show that the average fusion probability of release-ready vesicles varies among synapses supplied by the same axon with the size of the spike-evoked Ca²⁺ concentration transient. We further show that synapses with a high vesicular release probability exhibit a lower Ca²⁺ cooperativity, arguing that this is a direct consequence of increased Ca²⁺ influx at the active zone. We conclude that variability of neurotransmitter release under basal conditions at small central synapses is accounted for not only by the number of release-ready vesicles, but also by their fusion probabilities, which are set independently of bouton size by variable spike-evoked presynaptic Ca²⁺ influx.